First Report on Brorphine: The Next Opioid on the Deadly New Psychoactive Substance Horizon?. Issue 9 (3rd August 2020) - Verougstraete, Nick; Vandeputte, Marthe M; Lyphout, Cathelijne; Cannaert, Annelies; Hulpia, Fabian; Van Calenbergh, Serge; Verstraete, Alain G; Stove, Christophe
Abstract: New psychoactive substances continue to appear on the drug market. Until recently, new synthetic opioids, which are among the most dangerous new psychoactive substances, primarily encompassed analogs of the potent analgesic fentanyl. Lately, also other new synthetic opioids have increasingly started to surface. This is the first report on the identification and full chemical characterization of brorphine, a novel potent synthetic opioid with a piperidine benzimidazolone structure. A powder, identified as brorphine, was obtained from a patient seeking medical help for detoxification. Brorphine was also found in a serum sample of the patient. Liquid chromatography–high-resolution mass spectrometry (LC–HRMS) identified an exact mass of m/z 400.1020 and 402.1005 for the compound, corresponding to both bromine isotopes. Further chemical characterization was performed by gas chromatography–mass spectrometry, liquid chromatography–diode array detection and Fourier-transform infrared spectroscopy analyses. Finally, the structure was confirmed by performing 1 H-NMR and 13 C-NMR spectroscopy. In vitro biological activity of brorphine was determined by a cell-based µ-opioid receptor activation assay, resulting in an EC 50 of 30.9 nM (13.5 ng/mL) and an E max of 209% relative to hydromorphone, confirming the high potency and efficacy of this compound. In a serum sample of the patient, brorphine and a hydroxy-metabolite were found using the LC–HRMS screening method. The presence of opioid activity in the serum was also confirmed via the activity-based opioid screening assay. The occurrence of brorphine is yet another example of how the illicit drug market is continuously evolving in an attempt to escape international legislation. Its high potency poses a serious and imminent health threat for any user.